(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
Increasing the competitiveness of the warehouse - in the development of multimodal technology of transportation, increases the rate of international turnover of goods, lowers prices. Good warehouse management systems have been developed to ensure a reliable supply chain and a reliable supply chain.